Earth - Sharif-Draper, Maryam (London Dorling Kindersley Limited, 2017)
Find out all about the wonders of planet earth! Earth takes kids close to the all the wonders our planet holds with beautiful photography, lively illustrations, and key curriculum information. Find out all about the structure of the Earth, from its red-hot inner core to the mountains, deserts, and oceans that cover its surface. Discover why we have seasons, how the water cycle works, and why our population is
Science
1 2
Keywords: Earth (Planet) -- Juvenile literature; Earth sciences